In vitro Antiparasitic and Anti-severe Acute Respiratory Syndrome Coronavirus 2 Activities of Extracts and Fractions from Pouteria alnifolia - Mary Anti Chama; Jessica Asomaniwaa Armah; Nadia Alhassan; Gabriella Ama Amoakoma Essuman; Julius King Kwame Tuekpe; Zenabu Lansah Alidu; Amina Bukari; Fauzia Nurudeen; Ian Tietjen; Theresa Manful Gwira (Biomedical and Biotechnology Research Journal)
Background: Although there is widespread use of herbal medicine in many parts of the world including tropical Africa, scientific evidence to validate efficacy and safety is largely scarce. The aim of this study was to investigate the potential of Pouteria alnifolia as an alternative anti-infective. Methods: In this study, bioactivity-guided isolation of extracts from different parts of P. alnifolia was done, and the in vitro antitrypanosomal, antileishmanial, anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and cytotoxicity properties of the extracts and fractions were determined using the alamarBlue assay. Using microscopy, the growth kinetics of Trypanosoma brucei brucei was investigated by counting cells when parasites were exposed to different concentrations of selected extracts and fractions. Results: The results show that while anthracene and anthraquinone derivatives were absent in all the tested fractions, terpenoids, and cardiac glycosides were the most common phytochemicals in the fractions. Alkaloids were also detected in the dichloromethane (DCM) extracts of seeds and whole fruit (WF) compared to butanol (BuOH) fractions of the fruit pulp, stem, and roots. The IC50 values for T. b. brucei were between 07 ± 0.0 and 59.5 ± 0.3 µg/mL while that of Leishmania donovani ranged from 1.3 ± 0.1 to 27.8 ± 1.8 µg/mL. DCM extracts from WF, seeds, and stem inhibited the growth of T. b. brucei, whereas the BuOH fractions from seeds and WFs were most active against SARS-CoV-2. Conclusion: Extracts and fractions from P. alnifolia appear to have useful chemotherapeutic agents that warrant further study for a variety of infections faced by those in tropical Africa.